Salmonella enterica Serovar Typhimurium Expressing Mutant Lipid A with Decreased Endotoxicity Causes Maturation of Murine Dendritic Cells - Kalupahana, Ruwani (American Society for Microbiology, 2003)
A major Salmonella component involved in cellular activation is the lipopolysaccharide (LPS) molecule which can act as a dendritic cell (DC) stimulator. The structure of the lipid A domain of the LPS molecule dictates its immunostimulatory capacity with various cell types. In this study, the role of lipid A as an integral component of Salmonella in stimulating murine DCs was studied by using a Salmonella enterica serovar Typhimurium lpxM mutant with defective lipid A. This study revealed that a mutation in lpxM did not significantly affect the ability of bacteria to activate DCs. Although the lpxM mutant less tumor necrosis factor alpha, interleukin-1β, and inducible nitric oxide synthase than the parental strain, this was only seen at lower multiplicities of infection (MOIs). Both strains upregulated surface molecule expression on DCs and augmented the T-cell-stimulating capacity of these cells in an MOI-independent manner. Thus, the lpxM mutation did not appear to affect the stimulatory capacity of the Salmonella mutant.